(untitled) (Journal of Social Sciences Review, 2022)
: The main focus of present study was to examine effect of socio-economic status (social and financial support) upon the motivation of student-athletes of all public sector universities of Khyber Pakhtunkhwa Pakistan. The present study has also been focused upon mediating role of coach behavior in motivation the student-athletes. Cross-sectional research design was used for present study. The 1754 male and 190 female student-athletes were selected as population of the study. Three different extracted variables from the literature i.e. Socio-economic status (predictor) athlete motivation (criterion) and coach behavior (mediator). The polite testing was practiced for the purpose of reliability with help of Cronbach alpha coefficient. The Cronbach alpha score of socio-economic status scale was .729, coach behavior .729 and athlete motivation .843 which is fall in good zone. Personal visit was made for data collection by researcher. The return rate of responses was observed 90% (151 out 171). The process of Baron and Kenny approach was used for mediation with help of SPSS version 26 for analyses. The results of the current study indicated that there is a significant role of the coach behavior as mediator between the socio-economic status and athlete motivation of student-athletes. The results of the study also determined that socio-economic status have significant impact on athlete motivation level.